2010
DOI: 10.1002/macp.201000184
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic‐Salt‐Induced Morphological Transformation of Semicrystalline Micelles of PCL‐b‐PEO Block Copolymer in Aqueous Solution

Abstract: The effect of inorganic salt at concentrations typical of a biological environment on the micellar morphology of semicrystalline PCL‐b‐PEO in aqueous solution is investigated. The salt is introduced either by dialysis of a THF solution against an aqueous solution of the salt or by adding it into an aqueous solution containing preformed micelles. The inorganic salt can induce sphere‐to‐rod or sphere‐to‐lamella transformations of the PCL‐b‐PEO micelles in aqueous solution, depending on the length of the PCL bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 74 publications
4
76
0
Order By: Relevance
“…Many BCPs consisting of a long soluble block attached to a shorter crystallizable block 21 are potential candidates for this approach. While CDSA has been reported for BCPs with poly (3-hexylthiophene) 22 , polylactide 23 , polycaprolactone 24 and polyethylene 25 as the crystallizable block, one has the greatest control over this kind of seeded growth for polyferrocenylsilane (PFS) BCPs. Under appropriately chosen self-assembly conditions, all of the added unimer of a PFS BCP grow off the ends of the crystallite seeds in the sample, and uniform elongated structures can be formed [26][27][28][29][30][31] .…”
mentioning
confidence: 99%
“…Many BCPs consisting of a long soluble block attached to a shorter crystallizable block 21 are potential candidates for this approach. While CDSA has been reported for BCPs with poly (3-hexylthiophene) 22 , polylactide 23 , polycaprolactone 24 and polyethylene 25 as the crystallizable block, one has the greatest control over this kind of seeded growth for polyferrocenylsilane (PFS) BCPs. Under appropriately chosen self-assembly conditions, all of the added unimer of a PFS BCP grow off the ends of the crystallite seeds in the sample, and uniform elongated structures can be formed [26][27][28][29][30][31] .…”
mentioning
confidence: 99%
“…We added toluene to the aqueous solution of Au-Vbrushes and found that the Au-V-brushes stayed in the bottom water phase. After addition of a small amount of Na 2 SO 4 , which has a so-called ''salting-out'' effect and thus can reduce the solubility of the PEO block in water [48][49][50], the Au-V-brushes transfer into the upper toluene layer (Fig. 7a).…”
Section: Solubility Test and Phase Transfermentioning
confidence: 98%
“…6,9,10 The first rod-like micelles reported involved poly(ferrocenyldimethylsilane) (PFS) block copolymers. [11][12][13] Other more recent examples of rod-like micelles involve block copolymers with polyethylene (PE), 7,[14][15][16][17][18][19][20] polyacrylonitrile (PAN), 21 polyferrocenyldimethylgermane (PFG), 22 poly(e-caprolactone) (PCL), [23][24][25][26][27][28][29][30] poly(L-lactide) (PLLA), [31][32][33][34][35] and polythiophene, 36,37 as the crystalline core-forming block.…”
Section: Introductionmentioning
confidence: 99%
“…28 One study of PCL-b-PEO showed that exposure of spherical micelles in water to high ionic strength led to a morphological transition to lower curvature structures such as rods and lamellae. 26 The authors explained that ionic strength promotes contraction of the PEO chains due to salting-out, and in this way induced the change in morphology. A similar sphere-to-cylinder transformation was observed for aqueous micelles of PCL 66 -b-PEO 44 upon addition of base.…”
Section: Introductionmentioning
confidence: 99%